A Balanced Scorecard Approach for Evaluating Organizational Performance of Nepal Telecom (Management Dynamics, 2022)
A balanced scorecard approach is a common performance measuring system that employs performance metrics from financial and non-financial aspects. It describes an organization's current performance status and offers foundations for future performance. The study aims to assess the organizational performance of Nepal Telecom as a case study through the balanced scorecard. It adopted a quantitative research approach and employed secondary data to quantify Nepal Telecom's performance from 2016/2017 to 2020/2021. The study's findings revealed that Nepal Telecom's overall performance scores were 75, 83, 55, 45, and 47 out of 100 for the study periods. The first two years' performance score represented exceptional performance before the COVID-19 outbreak, and the last three years' performance represented average performance throughout the COVID-19 outbreak. Such findings empower managers to make a long-term decision that benefits the organization. Future scholars may carry out similar work using primary data sources since this study primarily uses secondary data sources.